2002
DOI: 10.1177/021849230201000203
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Bypass Surgery in Patients on Thyroxin Replacement Therapy

Abstract: The outcome of coronary bypass surgery was analyzed in 25 patients who were on thyroxin replacement therapy for chronic thyroid disorders at the time of operation. It was hypothesized that if such patients were given only their routine dose of thyroxin on the day of surgery, hemodynamic and cardiorespiratory recovery may be poor. All the patients on thyroxin replacement therapy were given their routine dose of thyroxin orally or via a nasogastric tube in the perioperative period. No supplemental dose was used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…[15] There are still conflicting data regarding the safety of CABG in untreated patients. Some authors have reported no adverse effects in patients with untreated mild-to-moderate hypothyroidism undergoing cardiac surgery, [16][17][18] whereas some others have suggested adverse effects such as severe myxedema after cardiac surgery, leading to significant hemodynamic compromise. [19] Some reports have also shown that percutaneous transluminal coronary angioplasty (PTCA) can be a better choice before CABG in hypothyroid patients who have a higher incidence of complications, if there is no time to render them euthyroid.…”
Section: Discussionmentioning
confidence: 99%
“…[15] There are still conflicting data regarding the safety of CABG in untreated patients. Some authors have reported no adverse effects in patients with untreated mild-to-moderate hypothyroidism undergoing cardiac surgery, [16][17][18] whereas some others have suggested adverse effects such as severe myxedema after cardiac surgery, leading to significant hemodynamic compromise. [19] Some reports have also shown that percutaneous transluminal coronary angioplasty (PTCA) can be a better choice before CABG in hypothyroid patients who have a higher incidence of complications, if there is no time to render them euthyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is the suggestion that hypothyroid subjects operated upon for spine surgery may have a 1-day increase in length of stay that was even much longer if the patient had poorly controlled diabetes mellitus [21]. This finding stands in contrast with that of Syed and co-workers who found that there was no significant outcome difference in patients with elevated TSH on thyroid supplement who underwent coronary bypass surgery [22] and to Sherman et al who found no effect on outcomes in hypothyroid patients undergoing angioplasty [23]. More recent data add further confusion to the outcome of surgery on hypothyroid patients.…”
Section: Discussionmentioning
confidence: 93%
“…The usual replacement dose can be administered on the day of surgery via the enteral route without the need for any additional supplementation or conversion to a parenteral route of administration. 38 There are no studies on the safety and efficacy of antithyroid medications (methimazole and propylthiouracil) in the perioperative period. To avoid the possible risk of thyroid storm in the perioperative period, these medications should be continued uninterrupted.…”
Section: Thyroid Medicationsmentioning
confidence: 99%